அழகிய பெரியவன் சிறுகதைகளில் சுற்றுச்சூழல் சிந்தனைகள் / Ecological Thoughts in the Short Stories of Azhagiya Periyavan - முனைவர் ஏ. கௌதமச்செல்வி / Dr. E. Gowthamaselvi (International Journal of Tamil Language and Literary Studies, 2023)
The short story is one of the fastest-growing literary genres due to the development of Tamil prose in the nineteenth century. Tamil short stories were written with day-to-day events happening in people's lives. Azhagiya Periyavan, a Tamil writer from Vellore district, has a passion for literature and community involvement. In this article, the study will find out the environmental thoughts found in his short stories. In this world created by God, various creatures, including humans, are living in harmony with nature. Natural resources are the resources that exist in nature without the intervention of humans on this earth consisting of the sun, atmosphere, water, land, minerals, plants and all animals. These include commercial, industrial utility, aesthetic value, scientific interest and cultural values. Although man gets all the basic needs for his life from nature, man is gradually destroying the earth by exploiting the natural resources due to his greed. This decomposition causes many pollutants in the surrounding environment. In today's modern age, we are not connected with nature but are interwoven with artificiality. If this situation continues, there is a danger that the human race will become extinct. So it is an important duty to preserve natural resources so that they can be used by future generations. This article is based on the ecological thoughts found in the short stories of Azhagiya Periyavan.